PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI DENGAN MENGGUNAKAN MEDIA GAMBAR - Idarliati, Idarliati (Institut Agama Islam Negeri Palopo, 2018)
The aim of this research was to find out the improvement of writing essay writing skills that were applied through the image media to the fifth-grade students of SDN 09 Mattekko kec. Bara City of Palopo. This study uses a quantitative and qualitative approach with a type of Classroom Action Research (CAR) designed through three cycles. The subject of the research was Mattekko 09 Elementary School Elementary School students, amounting to 24 students. Data collection techniques used are observation, documentation, and tests. Data obtained were analyzed using a descriptive statistical formula (percentage) to describe descriptively the results of the study. Furthermore, to discuss and explain the results of research that are qualitative descriptive, the data reduction analysis, data presentation, and conclusion drawing techniques are used. The results found that the pre-cycle stage, the average value of students was 58.54 with classical learning completeness of 20.5%. After learning to apply the picture media, in the first cycle, the average value was 67.70 with the classical completeness was 58.33%. Furthermore, in the second cycle, the average value was 74.58 with 79.16% classical learning completeness. Then, continued in the third cycle the average value is 81.45 with classical learning completeness is 95.83%. Thus, the skill of writing essays in the description of grade V students of SDN 09 Mattekko by applying picture media starting from the first cycle to the third cycle shows effective results. Therefore, the image media needs to be used as a reference by the teacher in learning to write essays in elementary schools, especially SDN 09 Mattekko, Palopo city.